1998
DOI: 10.1111/j.1600-079x.1998.tb00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between melatonin levels in plasma and gastrointestinal tissues and the incidence and severity of gastric ulcers in pigs

Abstract: Four weeks of administration of melatonin mixed in the diet (5 mg/kg of food) significantly reduced the incidence of gastric ulcers in young pigs. In control and melatonin supplemented animals, significantly higher levels of melatonin were found in the stomach tissues as compared to jejunum, ileum, or colon. Pigs with the most severe ulcers exhibited significantly lower concentrations of melatonin in their stomach tissue and the blood plasma. Pigs fed coarsely ground diet exhibited higher tissue levels of mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Although binding site parameters exhibited diurnal variation in some species, this was not confirmed in others [52,54,69]. In addition, large variations of melatonin concentrations in the individual segments of the GIT were found among many species of birds and mammals [9,35,38,44,57,64,66,[68][69][70]. Often, these tremendous variations of melatonin concentrations in GIT tissues appears to be related to food intake rather than to photoperiodicity as is the case of pineal-produced melatonin [41,70,71].…”
Section: Ontogeny and Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…Although binding site parameters exhibited diurnal variation in some species, this was not confirmed in others [52,54,69]. In addition, large variations of melatonin concentrations in the individual segments of the GIT were found among many species of birds and mammals [9,35,38,44,57,64,66,[68][69][70]. Often, these tremendous variations of melatonin concentrations in GIT tissues appears to be related to food intake rather than to photoperiodicity as is the case of pineal-produced melatonin [41,70,71].…”
Section: Ontogeny and Phylogenymentioning
confidence: 99%
“…As an injection or an alimentary administration of exogenous melatonin and its precursor tryptophan resulted in a significant accumulation of melatonin in the GIT [39,49,[55][56][57], it was initially questioned whether the presence of melatonin in the digestive system is due to its accumulation from the circulation (particularly during the night) or due to an independent synthesis in situ [49]. A significant diurnal variation of melatonin concentrations in some GI tissues (with plasma concentration much higher during the night) was reported by several authors in intact animals, mostly birds [52,[58][59][60].…”
Section: Ontogeny and Phylogenymentioning
confidence: 99%
“…The ulcers in this case may have been due to a local deficiency of the melatonin synthesis [7] . Recently, melatonin (combined with other natural supplements) was successfully used to heal a patient with a giant ulcer of 6 cm (about 3.2 inches).…”
Section: Clinical Usementioning
confidence: 78%
“…Bubenik et al [7] demonstrated that a 4-wk administration of melatonin in the diet significantly reduced the incidence of spontaneous gastric ulcers in young pigs. The ulcers in this case may have been due to a local deficiency of the melatonin synthesis [7] .…”
Section: Clinical Usementioning
confidence: 99%
“…The physiological role of the melatonin produced in the gut remains unclear. In the gastrointestinal system, melatonin relaxes the smooth muscles of the gut and blood vessels and increases mucosal blood flow, thus preventing the development or initiating the healing of gastric and intestinal ulcers [6,23,49,51,52]. It is also an effective agent against experimental colitis [48].…”
Section: Discussionmentioning
confidence: 99%